Obesity, Metabolic Health, and Diabetic Complications in People With Type 1 Diabetes - Yuanjie Mao; Jen‐Tzer Gau; Ning Jiang (Endocrinology, Diabetes & Metabolism)
ABSTRACT Aim The concept of metabolically healthy obesity (MHO) has not been studied in type 1 diabetes (T1D). By analysing datasets from the DCCT/EDIC study, we compared the development of diabetic complications by obesity and metabolic health over 30 years of follow up. Materials and Methods Insulin resistance was calculated by estimated glucose disposal rate (eGDR). The participants (n = 1127) were then divided into four groups based on time‐weighted mean body mass index and mean eGDR: metabolically healthy non‐obesity (MHN, n = 874), metabolically unhealthy non‐obesity (MUN, n = 66), MHO (n = 146) and metabolically unhealthy obesity (MUO, n = 41). Diabetic complications and cardiovascular events were compared across the four groups. Results MUO and MUN groups had significantly higher risk for peripheral neuropathy (p = 0.001 in MUO and p < 0.001 in MUN vs. MHN), cardiac autonomic neuropathy (p < 0.001 in both MUO and MUN vs. MHN), retinopathy (p = 0.001 in MUO and p < 0.001 in MUN vs. MHN) and microalbuminuria (p < 0.001 in both MUO and MUN vs. MHN) than MHN group. Moreover, MUO and MUN groups had significantly higher risks (HR [95%CI]) in any cardiovascular events (2.78 [1.51–5.11] and 1.88 [1.05–3.36]) and major atherosclerotic cardiovascular events (2.72 [1.16–6.37] and 2.31 [1.05–5.10]) compared to MHN group. However, the risk of these complications and cardiovascular events (except peripheral neuropathy and cardiac autonomic neuropathy) in MHO group was not different from that in MHN group. Conclusions This study highlights the importance of metabolic health represented by insulin resistance in the development of diabetic complications and cardiovascular events in T1D beyond their weight status.